On the value and limitations of incorporating a “clean phase” into the surgical treatment of prosthetic joint infections – an illustrative cadaveric study using fluorescent powder - Georges Vles; Jeroen Bossen; Johannes Kloos; Philippe Debeer; Stijn Ghijselings (Journal of Experimental Orthopaedics)
Abstract Purposes A septic revision of an artificial joint is routinely split up in a so‐called dirty phase and a clean phase. The measures taken to initiate the start of the clean phase vary significantly between musculoskeletal infection centers. We performed simulations of one‐step exchanges of infected THAs and sought to 1) determine the effect of different clean phase protocols on the sterile field, and 2) determine whether or not it is possible to re‐implant the new prosthesis completely clean. Methods Nine fresh frozen cadaveric hips were used and primary THA was undertaken via a direct anterior approach. Before implantation of the components varying amounts of fluorescent powder (GloGerm) were deposited, simulating bacterial infection. Second, a one‐step exchange was performed via a posterolateral approach. After implant removal, debridement, and lavage, randomization determined which clean phase protocol was followed, i.e. no, some or full additional measures. Finally, the new prosthesis was re‐implanted. In order to determine the effect of different clean phase protocols on contamination of the sterile field standardized UV light‐enhanced photographs were obtained of 1) the gloves, 2) the instrument table, 3) the drapes, and 4) the wound and these were ranked on cleanliness by a blinded panel of hip surgeons. In order to determine whether or not it is possible to re‐implant the prosthesis completely clean, the implant was taken out again at the end of the one‐step exchange and inspected for contamination under UV light. Results The gloves, the instrument table, the drapes and the wound were significantly cleaner after a clean phase using full additional measures compared to partial or no additional measures (p < 0.000). Partial measures were able to reduce some of the contamination of the gloves and the wound, but had no effect on the drapes and the instrument table. All re‐implanted implants were contaminated with some amount of fluorescent powder at the end of the one‐step exchange. Conclusions We advise to incorporate a clean phase with full additional measures into the surgical treatment of prosthetic joint infections, as partial measures seem to be a poor compromise. Level of evidence Not applicable (cadaveric study).